LEVER’S OF CONTROL DAN JEJARING SOSIAL SEBAGAI MEKANISME SISTEM PENGENDALIAN MANAJEMEN DALAM PENERAPAN STRATEGI DIFERENSIASI PRODUK - Barawidjaja Barawidjaja (AJAR, 2020)
This study aims to examine the effects of mediation from social networks and levers of control on product differentiation strategy to innovation. The population of this research uses a sample frame of the property company PT. Ciputra Graha Mitra and its subsidiaries which are national scale property development companies. Sources of data derived from the primary data collected from the managers or the head of the departement equal level with the manager at each company data obtained by conducting a survey of 123 respondents. This study indicates that social networking variables in mediating the relationship between product differentiation to innovation are No Mediation types, it can be concluded that social networking variables fail to function as intervening variables that mediate the influence of product differentiation strategies to innovation. However, the pattern of relationship between product differentiation strategy variables to innovation either through social networking variables or lever's control variables is positive, in this case the effect of product differentiation strategy variables to innovation through social networking variables or through levers of control variables can increase innovation but the effect is to weak.